The Role of Working Capital on Profitability After Tax on Automotive And Allied Products Companies in Indonesia: The Role of Working Capital on Profitability After Tax on Automotive And Allied Products Companies in Indonesia - Galih Wicaksono; Yeni Puspita (Institute of Computer Science (IOCS), 2020)
The purpose of this research is to know the role of working capital on profitability through factors that affect the amount of working capital, among others: Working capital turnover, liquidity, cash turnover, receivables turnover, turnover Stocks, and cash versus total assets, both partially and simultaneously. The data analysis method uses SPSS software with multiple regression analysis, which is used to test the tested hypothesis, both partially and simultaneously, and see the magnitude of the coefficient. Based on the results of the study and the discussion can be concluded that partially only the turnover of working capital and liquidity that have a significant impact on profitability, but the direction is negative. Simultaneously, the turnover of working capital, liquidity, cash turnover, receivables turnover, inventory turnover, and cash versus total assets affects profitability, but the effect is relatively small which is only 19.4%.